Premier Symposium International des Historiens de la comptabilité. Bruxelles 9-12 Octobre 1970. In memoriam Ernest Stevelinck 1909-2001 - Lemarchand, Yannick (De Computis, Revista Española de Historia de la Contabilidad., 2022)
Premier Symposium International des Historiens de la comptabilité, First World Congress of Accounting Historians, Brussels 9-12 October 1970, In memoriam Ernest Stevelinck 1909-2001